The Role of the Regional Supervisory Board in Enforcing the Notary Code of Ethics in Sragen Regency - Suyatmi, Suyatmi; Hafidz, Jawade (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to analyze: 1) The role of the Regional Supervisory Council in the implementation of the enforcement of the notary code of ethics in Sragen Regency. 2) Challenges of the Regional Supervisory Council (MPD) of Notaries in the framework of enforcing the code of ethics for notaries in Sragen Regency. This type of research is included in the scope of empirical research. The approach method in this study is a sociological legal approach. The types and sources of data in this study are primary and secondary data, obtained through interviews and literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1). The role of the Regional Supervisory Council in the implementation of the enforcement of the notary code of ethics in Sragen Regency is to ensure that notaries carry out their duties in accordance with the code of ethics and applicable laws and regulations. MPD functions as a supervisor and mentor, with the main task of providing guidance through socialization, training, and evaluation of notary performance in order to prevent violations. In addition, MPD also periodically supervises notary protocols and follows up on public complaints regarding alleged violations of the code of ethics or notary positions. As a supervisory institution, the MPD has the authority to hold hearings on alleged violations, grant leave permits, appoint replacement notaries, and determine the storage location for protocols that are 25 years oldormore. 2) Challenges of the Regional Supervisory Council (MPD) of Notaries in enforcing the code of ethics for notaries in Sragen Regency, namely the Regional Supervisory Council (MPD) of Notaries in Sragen Regency faces various challenges in enforcing the code of ethics, including limited authority, lack of resources, minimal supporting facilities, and low legal awareness among the community and notaries themselves. In addition, complex bureaucracy and a legal culture that is still developing also hamper the effectiveness of supervision. Therefore, it is necessary to strengthen regulations, increase the capacity of the MPD, optimize facilities, and provide legal education for the community and notaries in order to create more effective and professional supervision.Keywords: Code of Ethics Enforcement; MPD; Notary